2022
DOI: 10.1109/tvcg.2022.3209411
|View full text |Cite
|
Sign up to set email alerts
|

sMolBoxes: Dataflow Model for Molecular Dynamics Exploration

Abstract: Fig. 1. An overview of the sMolBoxes interface for molecular dynamics exploration, consisting of the 3D View, the Canvas with sMolBox Nodes, and the detailed bigBox View for navigation through the 3D animation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Recently, ( Ulbrich et al, 2023 ), presented sMolBoxes featuring a dataflow model designed for exploring and analyzing extended MD simulations. Through the integration of quantitative analysis for user-specified properties and interactive 3D visualizations, it facilitates the visual interpretation of molecular behaviors.…”
Section: General Considerations On Visualization Of Complex Molecular...mentioning
confidence: 99%
“…Recently, ( Ulbrich et al, 2023 ), presented sMolBoxes featuring a dataflow model designed for exploring and analyzing extended MD simulations. Through the integration of quantitative analysis for user-specified properties and interactive 3D visualizations, it facilitates the visual interpretation of molecular behaviors.…”
Section: General Considerations On Visualization Of Complex Molecular...mentioning
confidence: 99%
“…More recently, Ulbrich et al 17 ability to visualize each node in the expression tree. sMolBoxes exploits this to plot intermediate results from the operations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…More recently, Ulbrich et al 17 demonstrated the computation of user-defined properties through a visual node-based graph network instead of the typical scripting interface. A benefit of using visual nodes to construct expressions is the ability to visualize each node in the expression tree .…”
Section: Introductionmentioning
confidence: 99%